prove that area of equilateral triangle is root 3 by 4 into side square
Answers
Answered by
7
Let the each side be ' a ' units.
Semiperimeter = a+a+a/2
=3a/2
Area of triangle, using heron's formula
![= \sqrt{s(s - a)(s - b)(s - c)} = \sqrt{s(s - a)(s - b)(s - c)}](https://tex.z-dn.net/?f=+%3D+%5Csqrt%7Bs%28s+-+a%29%28s+-+b%29%28s+-+c%29%7D+)
![= \sqrt{ \frac{3a}{2} ( \frac{3a}{2} - a)( \frac{3a}{2} - a)( \frac{3a}{2} - a) } = \sqrt{ \frac{3a}{2} ( \frac{3a}{2} - a)( \frac{3a}{2} - a)( \frac{3a}{2} - a) }](https://tex.z-dn.net/?f=+%3D+%5Csqrt%7B+%5Cfrac%7B3a%7D%7B2%7D+%28+%5Cfrac%7B3a%7D%7B2%7D+-+a%29%28+%5Cfrac%7B3a%7D%7B2%7D+-+a%29%28+%5Cfrac%7B3a%7D%7B2%7D+-+a%29+%7D+)
![= \sqrt{ \frac{3a}{2}( \frac{3a - 2a}{2}) ( \frac{3a - 2a}{2}) ( \frac{3a - 2a}{2} )} = \sqrt{ \frac{3a}{2}( \frac{3a - 2a}{2}) ( \frac{3a - 2a}{2}) ( \frac{3a - 2a}{2} )}](https://tex.z-dn.net/?f=+%3D+%5Csqrt%7B+%5Cfrac%7B3a%7D%7B2%7D%28+%5Cfrac%7B3a+-+2a%7D%7B2%7D%29+%28+%5Cfrac%7B3a+-+2a%7D%7B2%7D%29+%28+%5Cfrac%7B3a+-+2a%7D%7B2%7D+%29%7D+)
![= \sqrt{ \frac{3a}{2} \times \frac{a}{2} \times \frac{a}{2} \times \frac{a}{2} } = \sqrt{ \frac{3a}{2} \times \frac{a}{2} \times \frac{a}{2} \times \frac{a}{2} }](https://tex.z-dn.net/?f=+%3D+%5Csqrt%7B+%5Cfrac%7B3a%7D%7B2%7D+%5Ctimes+%5Cfrac%7Ba%7D%7B2%7D+%5Ctimes+%5Cfrac%7Ba%7D%7B2%7D+%5Ctimes+%5Cfrac%7Ba%7D%7B2%7D+%7D+)
![= \frac{a}{2} \times \frac{a}{2} \sqrt{3} = \frac{a}{2} \times \frac{a}{2} \sqrt{3}](https://tex.z-dn.net/?f=+%3D+%5Cfrac%7Ba%7D%7B2%7D+%5Ctimes+%5Cfrac%7Ba%7D%7B2%7D+%5Csqrt%7B3%7D+)
![= \frac{ {a}^{2} }{4} \sqrt{3} = \frac{ {a}^{2} }{4} \sqrt{3}](https://tex.z-dn.net/?f=+%3D+%5Cfrac%7B+%7Ba%7D%5E%7B2%7D+%7D%7B4%7D+%5Csqrt%7B3%7D+)
=√3/4 a^2
Hence proved.
Semiperimeter = a+a+a/2
=3a/2
Area of triangle, using heron's formula
=√3/4 a^2
Hence proved.
Answered by
36
Here is your answer in the attachment
Attachments:
![](https://hi-static.z-dn.net/files/d4d/81b4d40ac4eb8dae9517788a1bfd2d37.jpg)
Similar questions